2008
DOI: 10.1161/strokeaha.107.496588
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Syndrome and Ischemic Stroke Risk

Abstract: Background and Purpose-More than 47 million individuals in the United States meet the criteria for the metabolic syndrome. The relation between the metabolic syndrome and stroke risk in multiethnic populations has not been well characterized. Methods-As part of the Northern Manhattan Study, 3298 stroke-free community residents were prospectively followed up for a mean of 6.4 years. The metabolic syndrome was defined according to guidelines established by the National Cholesterol Education Program Adult Treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
157
1
5

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 229 publications
(172 citation statements)
references
References 23 publications
5
157
1
5
Order By: Relevance
“…Furthermore, among nondiabetic subjects in NOMASS, those with elevated measurements of insulin resistance were significantly more likely to have a first ischemic stroke, even after adjusting for other risk factors and the metabolic syndrome [30]. The metabolic syndrome, a constellation of glucose dysmetabolism, obesity, hypertension, and dyslipidemia has been shown to independently confer greater risk of first and recurrent stroke [31,32]. It is unclear if metabolic syndrome confers a greater risk of first stroke than what one would expect for its components [33].…”
Section: Modifiable Medical Risk Factorsmentioning
confidence: 97%
“…Furthermore, among nondiabetic subjects in NOMASS, those with elevated measurements of insulin resistance were significantly more likely to have a first ischemic stroke, even after adjusting for other risk factors and the metabolic syndrome [30]. The metabolic syndrome, a constellation of glucose dysmetabolism, obesity, hypertension, and dyslipidemia has been shown to independently confer greater risk of first and recurrent stroke [31,32]. It is unclear if metabolic syndrome confers a greater risk of first stroke than what one would expect for its components [33].…”
Section: Modifiable Medical Risk Factorsmentioning
confidence: 97%
“…However, recent studies suggested that diet soft drink consumption may also be associated with health consequences, particularly type 2 diabetes and the metabolic syndrome, [4][5][6] risk factors for cardiovascular disease (CVD), ischemic stroke, and all-cause mortality. [7][8][9][10][11] A report from the Nurses' Health Study (NHS), which includes only women, showed an increased risk of coronary heart disease (CHD) with greater consumption of sugarsweetened beverages, and particularly soft drinks. 12 In that study, an increased risk of CHD was associated with diet soft drink consumption after adjustment for age only, but the association was no longer significant after adjusting for other cardiac risk factors.…”
Section: Introductionmentioning
confidence: 99%
“…Although metabolic syndrome has been recognized as a risk factor for atherosclerotic diseases such as coronary heart disease (2,3) and ischemic stroke (4)(5)(6)(7)(8), genetic risk for ischemic stroke in individuals with metabolic syndrome has remained uncharacterized. Given that stroke is the leading cause of severe disability and the third leading cause of death, after heart disease and cancer, in western countries and Japan (9), the identification of biomarkers for stroke risk is important both for risk prediction and for intervention to avert future events.…”
Section: Introductionmentioning
confidence: 99%